2023
DOI: 10.1108/lm-06-2023-0045
|View full text |Cite
|
Sign up to set email alerts
|

The state of embedded librarianship in the university research processes in selected African academic libraries

Anna Leonard,
Josiline Chigwada,
Gilbert Mushi

Abstract: PurposeThis study aims to examine the state of embedded librarianship in African academic libraries by exploring the extent of librarian embedment in research processes in selected academic libraries in Africa.Design/methodology/approachA survey was conducted to collect data using an online questionnaire. The study population was comprised of librarians who directly support researchers throughout the research process in the scholarly communication and information services sections. Purposive sampling was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Furthermore, Sun et al (2019), Deja and W ojcik (2021), and Leonard et al (2023) have indicated that embedded librarianship encompasses multiple roles including teaching, learning and research, collaboration, cooperation and more, to address the strategic objectives of an academic institution. There are numerous benefits to the practice of embedded librarianship.…”
Section: Embedded Librarianshipmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, Sun et al (2019), Deja and W ojcik (2021), and Leonard et al (2023) have indicated that embedded librarianship encompasses multiple roles including teaching, learning and research, collaboration, cooperation and more, to address the strategic objectives of an academic institution. There are numerous benefits to the practice of embedded librarianship.…”
Section: Embedded Librarianshipmentioning
confidence: 99%
“…Pospelova et al, 2018). Notably, librarians can also support researchers by providing information literacy programs, instructing them on accessing a wide range of information resources, and offering guidance on proper citation and referencing techniques (Leonard et al, 2023).…”
Section: Library Managementmentioning
confidence: 99%
See 3 more Smart Citations